Anti-inflammatory drug design by molecular hybridization approach - Bosquesi, Priscila Longhin [UNESP]; Melo, Tais Regina Ferreira [UNESP]; Vizioli, Ednir de Oliveira [UNESP]; Santos, Jean Leandro dos [UNESP]; Chung, Man Chin [UNESP] (MDPI, 2011)
The design of new drugs with better physiochemical properties, adequateabsorption, distribution, metabolism, and excretion, effective pharmacologic potency andlacking toxicity remains is a challenge. Inflammation is the initial trigger of severaldifferent diseases, such as Alzheimer s disease, asthma, atherosclerosis, colitis, rheumatoidarthritis, depression, cancer; and disorders such as obesity and sexual dysfunction.Although inflammation is not the direct cause of these disorders, inflammatory processesoften increase related pain and suffering. New anti-inflammatory drugs developed usingmolecular hybridization techniques to obtain multiple-ligand drugs can act at one or multipletargets, allowing for synergic action and minimizing toxicity. This work is a review of newanti-inflammatory drugs developed using the molecular modification approach.
Keywords: Anti-inflammatory; Hybridization; Multiple-ligands; Mutual prodrug